Reliability prediction of consumer computing applications : : doctoral thesis - Šilić, Marin 1983 (M. Šilić ;Fakultet elektrotehnike i računarstva, 2013)
SHORT SUMMARY: Consumer Computing is a novel consumer oriented methodology for development of component based applications. Consumers use existing applications as building blocks and compose them into more complex applications with the aim to support the additional desired functionalities. Besides the appropriate functionality, application’s nonfunctional properties such as reliability and availability might significantly impact the perceived quality of the application. The reliability of the application depends on various number of parameters that describe the context of the application usage. The additional challenge while determining the reliability of applications is a substantially large number of applications in Consumer Computing and a very limited subset of applications with known reliability values. To address this challenge, new statistical methods for prediction of applications reliability need to be proposed. Besides the accurate reliability predictions, the proposed methods should also support real-time prediction performance in order to be used during the selection of components while creating composite applications in Consumer Computing. -